The tumour microenvironment of the upper and lower gastrointestinal tract differentially influences dendritic cell maturation. - Dunne, Margaret; Lysaght, Joanne; Reynolds, John; Lynam-Lennon, Niamh (My University, 2020)
Background: Only 10-30% of oesophageal and rectal adenocarcinoma patients treated with neoadjuvant chemoradiotherapy have a complete pathological response. Inflammatory and angiogenic mediators in the tumour microenvironment (TME) may enable evasion of anti-tumour immune responses. Methods: The TME influence on infiltrating dendritic cells (DCs) was modelled by treating immature monocyte-derived DCs with Tumour Conditioned Media (TCM) from distinct gastrointestinal sites, prior to LPS-induced maturation. Results: Cell line conditioned media from gastrointestinal cell lines inhibited LPS-induced DC markers and TNF-α secretion. TCM generated from human tumour biopsies from oesophageal, rectal and colonic adenocarcinoma induced different effects on LPS-induced DC markers - CD54, CD80, HLA-DR, CD86 and CD83 were enhanced by oesophageal cancer; CD80, CD86 and CD83 were enhanced by rectal cancer, whereas CD54, HLA-DR, CD86, CD83 and PD-L1 were inhibited by colonic cancer. Notably, TCM from all GI cancer types inhibited TNF-α secretion. Additionally, TCM from irradiated biopsies inhibited DC markers. Profiling the TCM showed that IL-2 levels positively correlated with maturation marker CD54, while Ang-2 and bFGF levels negatively correlated with CD54. Conclusion: This study identifies that there are differences in DC maturational capacity induced by the TME of distinct gastrointestinal cancers. This could potentially have implications for anti-tumour immunity and response to radiotherapy.
PUBLISHED
Keywords: Dendritic Cells; Cancer Vaccines; Immunotherapy; Dendritic cell inhibition; Gastrointestinal cancer; Radiotherapy; TNF-α; Tumour conditioned media; Tumour microenvironment